Shaping the future of Kenya tax policy: Introducing the new Kenya tax CGE model - Omune, Lensa; Mbuthia, Juneweenex (CGIAR System Organization, 2024)
Kenya’s Medium-Term Revenue Strategy (MTRS FY2024/25-2026/27) which aligns to the Fourth Medium Plan (MTP 2023-2027), aims at raising sufficient resources for the delivery of Government’s priority programmes under the Bottom-up Economic Transformation Agenda. The strategy provides a comprehensive approach of effective tax system reforms to boost revenue collection and improve the tax system over the medium term.